Parathyroid hormone-related protein and somatolactin in sea bream (Sparus aurata) brain and pituitary - Ingleton, P. M. (2014)
Parathyroid hormone-related protein (PTHrP) and somatolactin (SL) are both peptides that have been located in PAS+ve pars intermedia (PI) cells of teleost fishes. In mammals and the chick PTHrP is a hypercalcaemic factor causing lysis of bone calcified matrix and inhibiting phosphate excretion via the kidney. Functions of PTHrP in fishes are unknown but SL stimulates phosphate re-absorption by flounder kidney tubule cells1 and low ambient calcium activates PI cells of trout pituitaries.2 It appears possible that both peptides have some similar functions. They only share incidental amino acid homologies, so we have examined brain and pituitaries of sea bream for their distribution using specific antiserum to chum salmon SL (generous gift of H. Kawauchi) and to two regions of human PTHrP (1–16 ) and (50–69).